Menorá: texto, configuração poética e reflexão teológica em Ex 25,31-40 - Carvalho, Ulisses Quintão de (2021)
This master’s dissertation carries out a detailed investigation into the literary form of Ex 25,31-40 by searching for elements that may confirm its belonging to the biblical genre of juridical poetry. Specific instructions for the manufacture of a lampstand that will compose the furniture of the Tabernacle and will also serve as an essential object in conducting the religious service are found in the excerpt. A specific study is carried out on each word that makes up the text and how they were combined to create the desired effect on those who would read or hear them first. Tables showing other manuscripts in which the text varies from the official standard version Hebrew Bible text are included, as well as the language in which they were written and their dating. Finally, the text is studied in its theological character so that it is possible to see what lies beyond the veil of the word and thus discover what it is thought there about God and His relationship to man, and whether, despite the millennia that separate today’s man from the dawn of such ancient monuments of literature, they may shed light on the present world and aid it in charting a brighter future